QUINTUPLE HELIX IN PUBLIC PRIVATE PARTNERSHIP (PPP) PROJECTS (Case Study – PPP’s Housing Project in Surabaya) - Karina Apriani; Eko Ganis Sukoharsono Sukoharsono; Noval Adib (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The demand for suitable and economical housing is on the rise due to the fast-paced growth of population and urban development. An innovative solution has been suggested to address this challenge, known as the Public Private Partnership (PPP) scheme. This research analyses the implementation of the Quintuple Helix concept in the Public Private Partnership (PPP) project of Vertical Housing in Surabaya. Using a qualitative methodology with a case study, this research identifies the key roles of the government, private sector, academia, community, and the environment in the success of the project. The results show that the Quintuple Helix approach is effective in optimising the implementation of PPP projects, but there are potential conflicts of interest between the helix, especially in terms of rental fees and quality standards. This research provides recommendations to improve communication, coordination, and collaboration between helixes, as well as strengthen the role of academia and community participation.